(untitled) (Tempo e Argumento, 2026)
The purpose of this article is to analyze the novel O som do rugido da onça, by Brazilian writer Micheliny Verunschk, published in 2021, in light of the provocations it aims at Brazilian historiography and literature, as well as the formation of their canons, as established in the nineteenth century. The novel has as premise recreating the story of the indigenous girl of the miranha people taken to Munich by Bavarian naturalists Carl Phillip von Martius and Johann Baptist von Spix after their expedition in Brazil between 1817 and 1820. Later, Martius was seminal to constitute a manner of narrating the history of Brazil, by winning, decades afterwards, a competition of the Instituto Histórico e Geográfico Brasileiro (IHGB) with the dissertation titled Como se deve escrever a história do Brasil (1843). I aim here to explore the questions posed by Verunschk’s work to this episode of Brazilian historiography as well as to the formation of the subfield of Theory of History in Brazil which took place in the last decades.